Assessing the future of African student mobility: Insights from forecasting models on international education dynamics - Shikaa, Samuel; Igiri, Chinwe Peace (Journal of International Students, 2026)
The global education landscape is transforming, with African nations playing a key role in international academic exchanges. However, future trends in African student mobility remain unclear. This study employs statistical, deep learning, and ensemble forecasting models to analyze migration patterns across regions: Central and Eastern Europe, Central Asia, East Asia and the Pacific, Latin America and the Caribbean, North America and Western Europe, South and West Asia, Sub-Saharan Africa, and the Arab States. Historical data reveals regional variations, with North America and Western Europe as top destinations, while East Asia, the Pacific, and the Arab States see rising enrollments. Intra-regional mobility within Sub-Saharan Africa highlights regional academic collaborations. These insights help institutions and policymakers anticipate trends, refine recruitment strategies, and enhance access to global education for African students, fostering knowledge exchange, skill development, and international collaboration.